Modal Analysis and Flight Validation of Compound Multi-Body Aircraft - Entong Zhu; Zhou Zhou; Huida Li (Aerospace, 2023)
The flight dynamics of a compound aircraft are highly coupled and significantly different from those of a single aircraft. In this paper, the characteristic flight dynamics of a three-unit connected aircraft are analyzed in detail. By distinguishing the aircraft’s modes into a symmetric mode group and an asymmetric mode group, the mechanisms by which the relative roll modes of the compound aircraft significantly impact the rigid-body modes of the vehicle become clear. The trim configuration of a compound aircraft has a profound influence on its stability and flight modes. In addition, the relative roll modes can be separated from the full-state model by appropriate simplifications, and the modal coupling mechanism and evolution law can be analytically derived. The key parameters which have a significant influence on the trim configuration and flight modes of the aircraft are pointed out in this paper. Finally, the common failure modes of compound aircraft are identified. A flight experiment with test data verifies the correctness of the above theoretical analysis.